Costs of meeting international climate targets without nuclear power - Vicki Duscha; Katja Schumacher; Joachim Schleich; Pierre Buisson (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
This paper assesses the impact of a global phase-out of nuclear energy on the costs of meeting international climate policy targets for 2020. The analyses are based on simulations with a global energy systems model. The phase-out of nuclear power increases greenhouse gas emissions by 2% globally, and 7% for Annex I countries. The price of certificates increases by 24% and total compli-ance costs of Annex I countries rise by 28%. Compliance costs increase the most for Japan (+58%) and the USA (+28%). China, India and Russia benefit from a global nuclear phase-out because revenues from higher trading volumes of certificates outweigh the costs of losing nuclear power as a mitigation option. Even for countries that face a relatively large increase in compliance costs, such as Japan, the nuclear phase-out implies a relatively small overall economic burden. When trading of certificates is available only to countries that committed to a second Kyoto period, the nuclear phase-out results in a larger increase in the compliance costs for the group of Annex I countries (but not for the EU and Australia). Results from sensitivity analyses suggest that our findings are fairly robust to alternative burden-sharing schemes and emission target levels.
Keywords: 330; nuclear power; phase out; climate policy; Post-Kyoto; Copenhagen pledges